2019
DOI: 10.1016/j.jid.2019.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Human Perifollicular Macrophages Undergo Apoptosis, Express Wnt Ligands, and Switch their Polarization during Catagen

Abstract: We would like to thank R Marotta/IIT for support with IM-TEM and acknowledge Kim Mace for reviewing the manuscript. This work was supported by grants from Unilever, UK, and the NIHR Manchester BRC (BRC-1215-20007) "Inflammatory Hair Diseases" program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…Additionally, qPCR results of upregulated mRNA levels of transcription factors (Axin2 and Lef1) further confirmed the function of translocated β-catenin in DP cells, by activating transcription factors important for anagen induction and maintenance. Our results are in agreement with a recent study, which showed that macrophages present near the hair follicles are positive for Wnt proteins, and also showed secreted Wnt10a near the DP cell and activates axin2 and Lef1 [21]. This study proved that Wnt3a/Wnt7b associated with MAC-EVs induced hair growth by activating receptors and relayed β-catenin cascade in DP cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, qPCR results of upregulated mRNA levels of transcription factors (Axin2 and Lef1) further confirmed the function of translocated β-catenin in DP cells, by activating transcription factors important for anagen induction and maintenance. Our results are in agreement with a recent study, which showed that macrophages present near the hair follicles are positive for Wnt proteins, and also showed secreted Wnt10a near the DP cell and activates axin2 and Lef1 [21]. This study proved that Wnt3a/Wnt7b associated with MAC-EVs induced hair growth by activating receptors and relayed β-catenin cascade in DP cells.…”
Section: Discussionsupporting
confidence: 93%
“…Another study showed that macrophages induce HF growth through tumor necrosis factor (TNF)-induced AKT/β-catenin signaling in Leucine-rich G-protein-coupled receptor 5 (Lgr5) + HF stem cells [20]. A recent study clearly showed that human perifollicular macrophages maintain the anagen stage in humans by activating DP cells by secreting Wnt proteins [21]. However, the effect of macrophage-derived EVs (MAC-EVs) on the activation of dermal papilla (DP) cells and hair growth is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mouse skin with all HFs in mid‐late anagen exhibits a profoundly immunoinhibitory milieu, 53,54 most likely due to the secretion of immunoinhibitory IP guardians by HFs. Further, the number, phenotype, apoptosis‐modulating activities and protein expression patterns of perifollicular macrophages significantly fluctuate during the human anagen‐catagen switch, 55 similar to observations in mice. 56 While it is as yet unclear what exactly this means for HF IP, it suggests that HF cycling can alter the local immune status of skin.…”
Section: The Biological Function Of Hair Follicle Immune Privilegesupporting
confidence: 73%
“…Currently, most of our understanding of the immune infiltrate during the human hair cycle is descriptive and confined to mostly anagen HFs, which is the predominant phase found in human scalps. Ex vivo analysis of human HFs is limited to anagen and catagen follicles, and telogen hairs are difficult to dissect and maintain in culture. Functional studies done in mice and small mammals have been extrapolated to human HF biology in order to develop new treatments, but actual mechanistic studies in humans are lacking.…”
Section: Discussionmentioning
confidence: 99%